The Flipped Classroom Learning Method in Enhancing Learning Independence: Literature Review - junaeda junaeda; Abdul Saman; Usman Bafadal (Journal of Innovative and Creativity, 2026)
The flipped classroom learning model has become a pedagogical innovation widely applied in modern education, primarily due to its ability to encourage active student engagement and enhance learning independence. This literature review aims to determine the effectiveness of flipped classrooms in improving students' self-regulated learning based on 10 empirical studies published in the 2019–2024 period. Articles were obtained from Google Scholar, ERIC, Scopus, and ScienceDirect databases with the inclusion criteria of studies examining flipped classrooms and learning independence in secondary and higher education contexts. The synthesis results indicate that flipped classrooms improve students' time management skills, learning strategy planning, self-reflection, intrinsic motivation, and self-efficacy. Pre-class activities through videos or digital modules have been shown to strengthen students' roles as independent learners, while face-to-face activities based on discussion and problem-solving enhance metacognitive abilities. However, successful implementation is influenced by technological readiness, digital literacy, the quality of pre-class materials, and teacher competence in designing interactive learning. This study confirms that flipped classrooms are effective in improving learning independence, but require technological support and thorough process planning to achieve optimal results.